Reconhecimento dos Antígenos Recombinantes MPT-51 e GlcB do Mycobacterium tuberculosis por Anticorpos Séricos de Indivíduos com Tuberculose Ativa - ALMEIDA, Cristina de Melo Cardoso (2007)
Tuberculosis (TB) caused by the Mycobacterium tuberculosis is responsible for more than 2 million deaths annually in the world. Although one third of the world population carries the bacilli, only 5% of the infected people develop active disease. 80% of TB cases are concentrated among 21 countries and Brazil is one of them. Due to the flaws existent inherent to the TB diagnostic, many works try to discover TB antigens to be used on an ELISA assay to detect active TB in underdeveloped countries, endemic for other mycobacterias such as leprosy (L). Several researches are identifying bacilli proteins obtained under nutritional culture stress, in order to mimic the intracellular milieu. It has been selected the immunodominant ones as a disease marker. The objective of this work was to characterize the humoral immune response among TB patients to rMPT-51 and rGlcB using an ELISA indirect test. It was included voluntaries that were HIV negative and the ones without pregnancy, chronic disease or under immunosuppressant treatment. Serum IgM and IgG against MPT-51 and GlcB recombinant antigen from 49 patients with active tuberculosis were measured by indirect ELISA, paired by sex and age with: healthy PPD negative individuals (controls) and lepromatous leprosy patients (LL). Patients with TB (0.810±0.319) showed higher levels of IgM against rMPT-51 than both LL individuals (0.454±0.195) and control (0.448±0.162) with statistical significant, p= 0.001 and p<0.001) respectively. These test showed 96.9% specificity and 67.3% sensitivity. Conversely, tuberculosis, controls, and LL individuals showed lower of MPT-51 IgG levels, which could not be distinguished among the groups. rGlcB antigen was able to distinguished TB patients from controls for IgM levels (specificity, 95.9 % and sensitivity, 8.2% ) and IgG levels (specificity, 99% and sensitivity, 18.2%). In order to evaluate the profiles of IgM and IgG against rMPT-51 and rGlcB before and after chemotherapy, the sera from 11 patients was collected and paired according to the treatment status (before or after). IgM and IgG against MPT-51 remained with the same profile levels before and after the treatment. The levels of serum IgG against rGlcB clearly diminished after the chemotherapy (p<0.01). Our results suggest that serum IgM levels against recombinant MPT-51 could to be useful to distinguish between active TB, controls and LL individuals. In addition, after TB treatment the IgG response to rGlcB diminished suggesting that it could be used to follow up of the TB treatment